58‐1: Invited Paper: Overcoming the Challenges in microLED Inspection and Manufacturing. Issue 1 (28th June 2021) - Lewis, David; Dechter, Rimma; Ley, Ryan; Wong, Matthew; Khoury, Michel
Abstract : MicroLED displays offer many advantages over existing display technologies, but manufacturing challenges remain before they can be commercially viable. InZiv is developing new microLED inspection tools with the highest resolution in optical, spectral, and structural characterization. This paper reviews critical challenges facing the industry and solutions to address them.